SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF COMMUNICATION AMONG PREVENTION INSPECTORS - Raxima Berdiyeva (Modern World Education: New Age Problems – New solutions, 2026)
This article explores the socio-psychological characteristics of communication among prevention inspectors, focusing on how interpersonal interactions, emotional intelligence, and social skills influence professional performance. The study analyzes theoretical frameworks related to social psychology, communication models, and organizational behavior to highlight how inspectors manage conflicts, motivate citizens, and implement preventive measures effectively. Special attention is given to stress management, empathy development, assertiveness, and ethical communication in law enforcement contexts. The role of professional training, peer support, and institutional culture in shaping communicative competence is also emphasized.